Malaysia : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Malaysia. (IMF Staff Country Reports; Country Report, 2009)
This 2009 Article IV Consultation highlights that Malaysia has been hit hard by the global downturn. The economy is set to contract for the first time in 10 years. Global turbulence has spilled into the domestic financial markets. Executive Directors have commended the Malaysian authorities for sound macroeconomic management in difficult circumstances. Directors have also emphasized that, although the financial sector appears sound and benefited from the growth of Islamic finance, volatile global markets put a premium on crisis preparedness and proactive supervision.